2017
DOI: 10.1111/pcmr.12644
|View full text |Cite
|
Sign up to set email alerts
|

Dual MEK/AKT inhibition with trametinib and GSK2141795 does not yield clinical benefit in metastatic NRAS‐mutant and wild‐type melanoma

Abstract: Aberrant MAPK and PI3K pathway signaling may drive the malignant phenotype in NRAS-mutant and BRAF NRAS metastatic melanoma. To target these pathways, NRAS-mutant and BRAF NRAS patients received oral trametinib at 1.5 mg daily and GSK2141795 at 50 mg daily in a two-cohort Simon two-stage design. Participants had adequate end-organ function and no more than two prior treatment regimens. Imaging assessments were performed at 8-week intervals. A total of 10 NRAS-mutant and 10 BRAF NRAS patients were enrolled. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Clinical investigations combining uprosertib with the MEK inhibitor trametinib in several cancers types have been underway, however, similar studies in multiple myeloma, melanoma and cervical cancer have revealed no clinical benefits of this combination. [43][44][45][46] Although uprosertib treatment as a monotherapy has been well tolerated, 22,23 the adverse toxicity profile of phase II combination studies has been deemed unacceptable, thus, uprosertib is not currently under further development. 46 Since we have demonstrated that enhanced OXPHOS in the presence of lactic acid is related to uprosertib resistance, and previous reports highlight that resistance to MEK combination therapies also corresponds with enhanced OXPHOS, 41 this metabolic phenotype should be considered as a possible contributor to the lack of clinical efficacy observed during phase II trials with uprosertib.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations combining uprosertib with the MEK inhibitor trametinib in several cancers types have been underway, however, similar studies in multiple myeloma, melanoma and cervical cancer have revealed no clinical benefits of this combination. [43][44][45][46] Although uprosertib treatment as a monotherapy has been well tolerated, 22,23 the adverse toxicity profile of phase II combination studies has been deemed unacceptable, thus, uprosertib is not currently under further development. 46 Since we have demonstrated that enhanced OXPHOS in the presence of lactic acid is related to uprosertib resistance, and previous reports highlight that resistance to MEK combination therapies also corresponds with enhanced OXPHOS, 41 this metabolic phenotype should be considered as a possible contributor to the lack of clinical efficacy observed during phase II trials with uprosertib.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pelitinib inhibit EGF-induced activation of AKT and ERK1/2 in cancer cells [37]. Uprosertib is used in recurrent or persistent ovarian cancer, endometrial cancer, and melanoma [38,39]. Uprosertib is a broad AKT inhibitor used not only for the treatment of gastric cancer, but also for AKT-dependent cancers [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pelitinib inhibit EGF-induced activation of AKT and ERK1/2 in cancer cells [36]. Uprosertib is used in recurrent or persistent ovarian cancer, endometrial cancer, and melanoma [37,38]. Uprosertib is a broad AKT inhibitor used not only for the treatment of gastric cancer, but also for AKT-dependent cancers [39].…”
Section: Discussionmentioning
confidence: 99%